STRATEGI WORD OF MOUTH MARKETING SOPHIE PARIS BC ASRIL DALAM MENINGKATKAN JUMLAH MEMBER YANG AKTIF - Nanda Risky; Rumyeni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Sophie Paris BC Asril is one of Multi Level Marketing (MLM) company that is usedword of marketing system in Pekanbaru city. This company uses member system in selling and get the profit. From more or less 17.000 Sophie Paris BC Asril’s members, it’s just about a half from all member be an active member. This condition will affect to company profit. Therefore the company need one of marketing strategy in order to increase the amount of active member. The purpose of this research is to know how word of mouth marketing strategy who created bybuzz and viralmarketing strategy, opinion leader role and social media role in Sophie Paris BC Asril’s to increase the amount of active member. This research used qualitative research method with descriptive approach. This reseach was done in Sophie Paris BC Asril, addres in Gelugur Street No.39, Middle Tangkerang subdistrict, Pekanbaru City. The object of this research is word of mouth communication strategy and the subject are all of the informants that are fullfil the needed of this research and the key informant is the leader, employees and some members of Sophie Paris BC Asril with purposive method.. Taking data technique in this research is by using deep observation, interview and documentation. The result of this research is describes word of mouth marketing strategy who created by three dimension there arebuzz andviral marketing, opinion leader and social media, who used by Sophie Paris BC Asril in order to increase the amount of active member. Buzz and viral marketing who done is like holding a bazar and event in the shopping center.As opinion leader in Sophie Paris BC Asril is Mrs. Asril who also the owner of the BC, because Mrs. Asril is a person who trusted and be a role model for the membership, due to her knowledge and experience which have long been in the business. Sophie Paris BC Asril also did not miss the technology in conducting its business, because they know very well by utilizing social media such as twitter, facebook, online shopp and others will expand its network and ease in socializing, interaction, sharing of information between fellow member and owner of the company and make it easier to access the member who want to find out company information. Keywords : Member, Sophie Paris, Word Of Mouth